2020
DOI: 10.20886/jai.2020.3.2.77-88
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Of Soil Macrofauna On Several Land Use On Peatlands

Abstract: Lahan gambut sangat rentan terhadap perubahan fungsi lahan. Pemanfaatan lahan gambut yang ditemukan (Beberapa kondisi tutupan lahan gambut) saat ini diantaranya lahan budidaya pertanian, perkebunan, semak belukar dan hutan sekunder. Kehadiran makrofauna tanah sebagai perekayasa ekosistem tanah dapat digunakan sebagai salah satu bioindikator kesuburan lahan gambut. Penelitian ini bertujuan untuk menganalisis keanekaragaman makrofauna tanah pada beberapa pola penggunaan lahan gambut di kawasan budidaya. Peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Similarly, the secondary peatlands located in West Kalimantan exhibit a medium level (H' = 2.09). According to Handayani and Winara (2020), the level of macrofauna diversity in oil palm farms is comparatively reduced, with a recorded Shannon diversity index (H') value of 0.73. According to Gesriantuti et al (2016), the diversity in burnt peatlands with an acacia monoculture restoration (H' = 0.48) is higher compared to the diversity observed in forest types with heterogenous protection (H' = 0.31).…”
Section: Agroforestry and Biological Activities In Of Peat Soilsmentioning
confidence: 99%
“…Similarly, the secondary peatlands located in West Kalimantan exhibit a medium level (H' = 2.09). According to Handayani and Winara (2020), the level of macrofauna diversity in oil palm farms is comparatively reduced, with a recorded Shannon diversity index (H') value of 0.73. According to Gesriantuti et al (2016), the diversity in burnt peatlands with an acacia monoculture restoration (H' = 0.48) is higher compared to the diversity observed in forest types with heterogenous protection (H' = 0.31).…”
Section: Agroforestry and Biological Activities In Of Peat Soilsmentioning
confidence: 99%
“…As explained above, vegetable protein is no less effective than protein obtained from meat [14,17]. Such vegetable protein can be obtained from tempeh, a traditional food commonly consumed in Indonesia [18,19]. In a study, it was shown that resistance exercise, especially eccentric exercise, causes muscle damage, as evidenced by increasing creatine kinase (CK) levels, muscle soreness, and reduced muscle strength [20].…”
Section: Introductionmentioning
confidence: 99%